2023
DOI: 10.1002/cpe.7843
|View full text |Cite
|
Sign up to set email alerts
|

An efficient fuzzy‐based task offloading in edge‐fog‐cloud architecture

Abstract: In a hierarchical edge‐fog‐cloud architecture, edge devices possess limited resources and energy. To contain with, it can offload some tasks generated by the Internet of Things (IoT) to the fog and cloud. Several factors influence this task‐offloading decision, including hardware features, network conditions, and application characteristics. Most of the research studies, in task offloading systems, have confined to changing parameter values, whereas very few have considered fuzzy‐based dynamic approaches for r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…This will help to deliver real-time energy services at the edge of the smart grid. The dynamic nature of resources in IoT computing farms needs a more robust control mechanism to ensure efficient operation [79]. The offloading architecture aims to minimize the delay while considering energy consumption limitations, and algorithms have been suggested to optimize the delay [80].…”
Section: Computational Requirementsmentioning
confidence: 99%
See 1 more Smart Citation
“…This will help to deliver real-time energy services at the edge of the smart grid. The dynamic nature of resources in IoT computing farms needs a more robust control mechanism to ensure efficient operation [79]. The offloading architecture aims to minimize the delay while considering energy consumption limitations, and algorithms have been suggested to optimize the delay [80].…”
Section: Computational Requirementsmentioning
confidence: 99%
“…Computational Requirements CPU, Memory, HDD, Devices, Processing Capabilities Processing node selection [75], models based on task nature [77], C-RAN architecture, adaptive algorithms, edge devices offloading [78], control mechanisms [79], offloading architecture [80], computation offloading in cloud robotics [81] Influencing feasibility and efficiency of offloading tasks, dynamic adjustment, and trade-offs between local execution and cloud offloading [80].…”
Section: Location and Data Characteristics Location Data Volume Veloc...mentioning
confidence: 99%
“…Request ET (R ET ) is the time involved between R est and request execution finish time ( R eft ) , which is calculated as R ET = R eft − R est . The average ET (A ET ), of a given batch of RT and NRT requests, is computed using Equation (2).…”
Section: Minimum Execution Timementioning
confidence: 99%
“…However, it has been observed that the Cloud-based services may require more time to respond which sometimes are not feasible for the requests requiring ultra-low latency such as RT/IoT requests. 2 Fog computing addresses these challenges well and fills the gap between Cloud and IoT applications by enabling computing, storage, and networking infrastructure near the IoT devices. 3 In a three-tier architecture, Fog computing lies between Cloud and IoT/edge devices.…”
Section: Introductionmentioning
confidence: 99%